PyPhase – a Python package for X‐ray phase imaging - Langer, Max; Zhang, Yuhe; Figueirinhas, Diogo; Forien, Jean-Baptiste; Mom, Kannara; Mouton, Claire; Mokso, Rajmund; Villanueva-Perez, Pablo (Journal of synchrotron radiation, 2021)
X‐ray propagation‐based imaging techniques are well established at synchrotron radiation and laboratory sources. However, most reconstruction algorithms for such image modalities, also known as phase‐retrieval algorithms, have been developed specifically for one instrument by and for experts, making the development and diffusion of such techniques difficult. Here, PyPhase, a free and open‐source package for propagation‐based near‐field phase reconstructions, which is distributed under the CeCILL license, is presented. PyPhase implements some of the most popular phase‐retrieval algorithms in a highly modular framework supporting its deployment on large‐scale computing facilities. This makes the integration, the development of new phase‐retrieval algorithms, and the deployment on different computing infrastructures straightforward. Its capabilities and simplicity are presented by application to data acquired at the synchrotron source MAX IV (Lund, Sweden). PyPhase is a free and open‐source Python package for propagation‐based near‐field phase reconstructions, which implements some of the most popular phase‐retrieval algorithms in a highly modular framework supporting the deployment on large‐scale computing facilities. This makes integration, development of new phase‐retrieval algorithms, and the deployment on different computing infrastructures straightforward.